Creating Lexical Resources in TEI P5 - Gerhard Budin; Stefan Majewski; Karlheinz Mörth (Journal of the Text Encoding Initiative)
Although most of the relevant dictionary productions of the recent past have relied on digital data and methods, there is little consensus on formats and standards. The Institute for Corpus Linguistics and Text Technology (ICLTT) of the Austrian Academy of Sciences has been conducting a number of varied lexicographic projects, both digitising print dictionaries and working on the creation of genuinely digital lexicographic data. This data was designed to serve varying purposes: machine-readability was only one. A second goal was interoperability with digital NLP tools. To achieve this end, a uniform encoding system applicable across all the projects was developed. The paper describes the constraints imposed on the content models of the various elements of the TEI dictionary module and provides arguments in favour of TEI P5 as an encoding system not only being used to represent digitised print dictionaries but also for NLP purposes.